Anesthesia for Pediatric Deep Brain Stimulation - Joseph Sebeo; Stacie G. Deiner; Ron L. Alterman; Irene P. Osborn (Anesthesiology Research and Practice)
In patients refractory to medical therapy, deep brain stimulations (DBSs) have emerged as the treatment of movement disorders particularly Parkinson's disease. Their use has also been extended in pediatric and adult patients to treat epileptogenic foci. We here performed a retrospective chart review of anesthesia records from 28 pediatric cases of patients who underwent DBS implantation for dystonia using combinations of dexmedetomidine and propofol-based anesthesia. Complications with anesthetic techniques including airway and cardiovascular difficulties were analyzed.